“From the football pitch to the boardroom”: a comparative analysis of talent coaching through neuroscience and its application in business leadership - Lambridis, Nikos (Frontiers in Organizational Psychology, 2025)
By drawing parallels between the latent coaching dynamics in the high-stakes global segment of football and the difficult segment of business leadership, the research is focused on a comparative evaluation to examine the transferability of coaching principles “from pitch to boardroom”. This study investigates and evaluates the transferability of talent coaching principles from football to business leadership by establishing a model for adopting successful talent management strategies in a corporate context. A comparative case study was used to develop an in-depth evaluation of the principles of talent coaching in business and football leadership. The comparative analysis showed that both domains prioritize nurturing and identifying individual strengths, promoting effective teamwork and communication, and stimulating a growth mindset. Furthermore, strategies, including continuous improvement, feedback mechanisms, and goal setting, seem to be key to both aspects. These results highlight the possibility of cross-disciplinary learning between business and football leadership in talent coaching. Therefore, while few strategies are applicable in both contexts, general principles, including skill development, empowerment, and motivation, seem applicable to both domains. Such a comparative evaluation emphasizes the synergies between diverse talent coaching processes in business and football leadership and reinforces valuable insights. Moreover, organizations need to optimize their talent development strategies and stimulate a culture of excellence, akin to that found in elite sports. Finally, we provide two coaching models for implementation, one for trainers (POSITIVE) and one for parents (AAAA) as a practical follow-up guide for the Organization/Athletic Club. The pilot ground for this research is the Athletic Club Palaio Faliro in Athens, Greece.